Aid Effectiveness Agenda and the Politics of Ownership in Donor-Recipient Relationships - Paksi, Arie Kusuma (Journal of Islamic World and Politics, 2019)
This article argues the political factors behind aid implementation continuously become dominant motive in donor-recipient relationships. Thus this makes the effort to effective aid which already started since post-Cold War era did not really find significant achievements. Although in the Paris meeting aid communities regards the idea of ownership as a new effort to effective aid intervention in developing countries, however, once again, the issue of power and politics remain hidden in the discussion. In fact, ownership has political dimension in which it involves power and interest among actors. In this context, each development actor is in position to win ‘ownership’ over development according to their agenda. Thus, this makes aid effectiveness agenda, once again, did not fully achieve much progress